Platforms without borders: Envisioning a multistakeholder platform for the whole Incomati Basin - Nehring, Ryan; Joaquim, Dominic; Lautze, Jonathan F. (CGIAR, 2024)
While multistakeholder platforms (MSPs) are proliferating in shared waters, there is a diversity of approaches with little comparison or shared learning between them. This CGIAR Initiative on NEXUS Gains webinar reviewed experiences in transboundary MSPs, presented a proposed design for a new transboundary MSP in the Incomati Basin, and facilitated discussion on the suitability of that design. The webinar included a roundtable discussion of notable MSP practitioners, offering relevant lessons for MSP development in other shared watercourses, including the Incomati Basin.